PERSEPSI MASYARAKAT DESA SENAKIN TERHADAP KEBERADAAN RIAM SOLANG SEBAGAI HUTANWISATA ALAM KECAMATAN SENGAH TEMILA KABUPATEN LANDAK - Rikardo, Riki; Dirhamsyah, M.; Yani, Ahmad (Universitas Tanjungpura, 2016)
The area of Solang Cascade need to be conserved and in managedbecause in addition being a nature tourism forest andan area for flora and fauna to thrive, it also serves as economic income for the communities around the area. Therefore, there is a need to cooperateamong members of the community and assistance from government such as the Ministry of Forestry or Ministry of Tourism. This research was carried out in SenakinVillage,Subdistrict of Sengah Temila,Landak Regency, West Kalimantan Province.The research aims to find outthe Senakin villagers’ perception of Solang cascade management as Nature Tourism and to identify the factorsthat affect such perception. The research is expected to provide input as reference material or consideration formaking management strategies. The method used was a survey method which was descriptive and associative in nature with questionnaires and interviews where samples / respondents wereselected through pusposive sampling technique under certain consideration.The number of samples taken as respondents was 100 households. The calculation of Chi Square resulted in the value of 42.98 and the table value at the significant level (0.05) was 5.591. Since the value of X2count>the value ofX2table​​(0.05) then the descriptive hypothesis was accepted. This indicates that the frequency of the villagers’ perception of the management Solang Cascadein Senakin Village tends to be different. Keywords : Nature Tourism. Solang Cascade, Villagers’Perception.